2011
DOI: 10.1097/01.pra.0000407962.49851.ef
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Diagnosis of Bipolar Disorder in Individuals of African and European Descent

Abstract: Despite efforts to curtail the phenomenon, racial disparities in diagnosis of bipolar disorder persist. Racial and cultural elements may affect how patients manifest behaviors and symptoms and how these are interpreted and attributed by clinicians in the diagnostic process. As an appropriate diagnosis determines treatment options and is central to quality of care, incorrect diagnosis can potentially have a negative impact on treatment effectiveness and accuracy of prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
(131 reference statements)
0
2
0
Order By: Relevance
“…These differences have been observed in the general population before, and are likely due to differential presentation of symptomology, access to and participation in mental health care, and bias in diagnostic procedures for people of different race or ethnicity. 35…”
Section: Resultsmentioning
confidence: 99%
“…These differences have been observed in the general population before, and are likely due to differential presentation of symptomology, access to and participation in mental health care, and bias in diagnostic procedures for people of different race or ethnicity. 35…”
Section: Resultsmentioning
confidence: 99%
“…While individual studies of both cardiovascular and neurologic symptoms demonstrated diagnostic disparities linked with ethnicity or insurance status, in pooled analysis, no consistent associations were identified. These findings add to the growing evidence base of diagnostic disparities across many clinical conditions such as delayed appendicitis diagnosis in Black children, overdiagnosis of schizophrenia in Black individuals, and delayed dementia diagnosis in Asian and Hispanic/Latinx individuals 4–9…”
mentioning
confidence: 77%
“…Validated by empirical data, disparities of race prevail in diagnosing acute types of psychopathologies (Becker et al, 2022) [4] . Haeri et al, 2011 [14] , indicated a higher prevalence of more severe personality disorders in individuals identifying as ethnic or racial minorities, while (Garb, 2021) [13] evidences different mental health conditions are diagnosed with racial bias. No exception, bias in BPD diagnosis can be marked within certain minority populations.…”
Section: Review Of Population and Dominant Groupsmentioning
confidence: 99%
“…The stated results in black American women presenting with more acute and explicit symptoms such as lacking emotional and impulse control while white women with BPD are more likely to present with more illicit symptoms such as suicidal ideations/actions and self-harming behaviors. Consistent with the prognosis and treatment of healthcare conditions, factors such as race, socioeconomics, and the ensuing discriminatory encounters one endures, are often cause for the stated consequences of misdiagnosis and poor fit treatment practices to be marked with more frequency in populations with less power (Becker et al, 2022;Haeri et al, 201) [4,14] .…”
Section: Review Of Population and Dominant Groupsmentioning
confidence: 99%
See 1 more Smart Citation